The chaos of empire : the British Raj and the conquest of India - Wilson, Jon E. (New York, Public Affairs, 2016)
"Through the stories of administrators, soldiers and subjects, describes how the East India Company went from a trading company to a quasi-imperial government with over a quarter of a million troops, whose high tax on tea helped spark the American Revolution,"--NoveList
Preface: Facts on the ground -- Society of societies -- Trading with ghosts -- Forgotten wars -- Passion at Plassey -- New systems -- Theatres of anarchy -- The idea of empire -- Fear and trembling -- The making of modern India -- The legalization of India -- The great Depression -- Governments within governments -- Military imperialism and the Indian crowd -- Cycles of violence -- The great delusion
Includes bibliographical references (pages 505-544) and index
Keywords: British -- India -- History; India -- History -- British occupation, 1765-1947.; India -- Civilization -- British influences; History